Patterns and Failure Modes of Fractures Resulting From Forced Folding of Cohesive Caprocks – Comparison of 2D vs. 3D and Single-vs. Multi-Layered Analog Experiments - Warsitzka, Michael; Kukowski, Nina; May, Franz (Frontiers in Earth Science, 2022)
Knowledge of the formation mechanisms and geometries of fracture systems in sedimentary rocks is crucial for understanding local and basin-scale fluid migration. Complex fracture networks can be caused by, for instance, forced folding of a competent sediment layer in response to magmatic sill intrusion, remobilisation of fluidized sand or fluid overpressure in underlying porous reservoir formations. The opening modes and geometries of the fractures mainly determine the bulk permeability and sealing capacity of the folded layer. In this study, we carried out laboratory analog experiments to better comprehend patterns and evolution of the fracture network during forced folding as well as differences of the fracture patterns between a 2D and 3D modelling approach and between a homogenous and a multi-layered cover. The experimental layering consisted of a lower reservoir layer and an upper cover, which was either a single high-cohesive layer or an alternation of low- and high-cohesive layers. The two configurations were tested in an apparatus allowing quasi-2D and 3D experiments. Streaming air from the base of the model and air injected through a needle valve was used to produce a regional and a local field of fluid overpressure in the layers. The experimental outcomes reveal that the evolution of the fracture network undergoes an initial phase characterized by the formation of a forced fold associated with dominantly compactive and tensile fractures. The second phase of the evolution is dominated by fracture breakthrough and overpressure release mainly along shear fractures. Structures observed in 2D cross sections can be related to their expressions on the surface of the 3D respective experiments. Furthermore, the experiments showed that the intrusion network is more complex and laterally extended in the case of a multi-layered cover. Our results can be instructive for detecting and predicting fracture patterns around shallow magmatic and sand intrusions as well as above underground fluid storage sites.